Cultural and Wellness Tourism: The Potential of Yoga, Meditation and Self-Purification Ceremony - Ida Bagus Nyoman Mantra; I Nyoman Suparsa; Nengah Dwi Handayani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Cultural and wellness tourism is one of the tourism assets that can be developed to support sustainable tourism. Yoga, meditation, and self-purification are components of Balinese culture that are practised by many Indonesians and foreigners alike. Yoga, meditation, and self-purification activities can be used to promote cultural and wellness tourism to attract domestic and foreign tourists. This research was conducted to determine whether yoga, meditation, and self-purification activities support cultural tourism in Bali. The research method used is a qualitative method where data were collected through interviews and field observations. The data were then analyzed descriptively. This study found that yoga, meditation, and self-purification activities can be used to promote cultural and wellness tourism in Bali. This research has implications that yoga, meditation, and self-purification activities can be designed to be used for sustainable cultural tourism activities and can also be used for attractive promotional media.